Fragmented tribes of the India-Burma-Bangladesh borderlands: representation of the Zo (Kuki-Chin) people in colonial ethnography - Pau, Pum Khan; Mung, Thang Sian (Asian ethnicity, 2022)
In the absence of pre-colonial written records, reconstruction of the history and identity of indigenous tribes has to depend on oral stories and the documentation of the 'other', while the former is subject to distortion, the latter is often glossed with vested interest. Taking the case of the indigenous tribes of the India-Burma-Bangladesh borderlands, this paper probes the representation of the Zo (Kuki-Chin) people in colonial ethnography, on one hand, and to what extent colonial knowledge was informed by 'investigative' or 'survey modality', which, in fact, was solely for administrative purpose, on the other. It argues that indigenous tribes of the India-Burma-Bangladesh borderlands were represented as completely fragmented in colonial ethnography, however, behind the colonial policy of classification one can still unearth the ethnic commonality of the various tribes when they are seen through the lens of cultural similarity or as a 'culture area.'